Constructing a Political Crime: Songs about the Assassination of the duc and the cardinal de Guise. Issue 1 (2nd January 2019) - Debbagi Baranova, Tatiana
Abstract : Songs played a significant role in the French Wars of Religion by spreading political and religious ideas, and by involving Protestants and Catholics in the conflict. Performed in the streets, churches, workshops and houses, songs participated in the construction of urban soundscapes during the troubles. This article examines six songs composed after the execution of the duc and the cardinal de Guise on the order of Henri III (23 and 24 December, 1588) and printed in Paris by Nicolas Bonfons. This event sparked the armed revolt of the Catholic League against the king and his heir, the Protestant Henri de Navarre. The article analyses the rhetorical features of the songs and compares their arguments with those of contemporary visual images and printed libels. In particular, it shows how songs served as a link between print and oral culture. Songs allowed Leaguers — whatever their age, sex, or status — not only to assimilate the main points of the justification of the revolt and to incorporate representations of a just monarchy, but also to appropriate them intimately by singing.